Markers of endometrial receptivity: a study of ultrasonographic and molecular factors - Polanski, Lukasz T. (2016)
The evidence suggests that alteration of the endometrial environment in women with previous failed in vitro fertilization (IVF) or intra-cytoplasmic sperm injection (ICSI) by inflicting endometrial injury improves the outcome of the subsequent treatment cycle. The selected population assessed in the studies supporting this statement prevents from generalizing this to all women undergoing IVF or ICSI treatment. The mechanisms responsible for alteration of the endometrial environment following biopsy remain still unclear. If proven effective, endometrial injury could serve as a beneficial adjunct for all couples undergoing assisted reproductive treatment (ART).